A contribuição do ranking universitário UI Greenmetric de sustentabilidade para a Universidade de Passo Fundo - Reginatto, Giovana (2022)
With the countless environmental problems faced daily around the world, promoting sustainable development is essential. Higher Education Institutions (HEIs) are allies in the dissemination of knowledge about sustainability, playing an important role. Many HEIs are concerned and committed to becoming more sustainable, developing actions and strategies that incorporate sustainable development, both in their infrastructure, teaching, research and extension. University rankings, in turn, are important tools that help universities measure sustainability on their campuses, as is the case with the UI GreenMetric university sustainability ranking. Therefore, the objective of this research is to analyze the contribution of the UI GreenMetric university sustainability ranking to the University of Passo Fundo (UPF). This research identified the good practices that universities are carrying out, as well as analyzing the recent inclusion of the UPF in the ranking in 2020 and 2021, seeking to propose improvements, with the aim of further improving the classification. The work methodology is divided into four stages. First, the best practices of universities participating in the 2020 virtual ranking workshop were identified. Next, an exploratory study was carried out at the Universidade São Paulo (USP), identifying the actions that the university adopts, as it is the first Brazilian university ranked in the ranking. The third stage was the case study at the UPF, in which the results of the UPF ranking in 2020 to 2021 were characterized, followed by a focus group, with the sectors involved in the ranking process. And finally, based on the previous methodological steps, an action roadmap for the UPF was developed. The results demonstrated that the UPF has the potential to boost its ranking, but needs planning regarding the process. With the action script, it was possible to identify the main challenges in the ranking process, creating a flowchart of responsibilities, with the aim of causing possible improvements applicable to the institution. Therefore, this work aims to contribute to the implementation of initiatives that boost the UPF's classification in the ranking, generating national and international notoriety and recognition for the institution.